Analysis of Collaborative Governance in Handling Rape Cases in Aceh: A Case Study in Banda Aceh City - Maghfirah Izzani; Nofriadi; Effendi Hasan; Wais Alqarni; Mukhrijal (PT. Global Research Collaboration, 2026)
This study examines the implementation of collaborative governance in handling rape cases in Banda Aceh City, Indonesia. The increasing number of reported cases, alongside persistent challenges in evidence collection, victim trauma, and institutional coordination, underscores the need for an integrated multi-stakeholder approach. This study employed a descriptive qualitative method through in-depth interviews with two key institutional informants representing DP3AP2KB through UPTD PPA and the Banda Aceh Police. The interview findings were supported by documentary triangulation consisting of institutional Standard Operating Procedures (SOPs), referral records, service statistics, and Case Conference reports. The findings indicate that, from the perspectives of the two institutional informants, collaboration in rape case handling is perceived as relatively structured and functional through the existence of formal coordination mechanisms, facilitative leadership, inter-agency communication, and a relatively clear distribution of institutional roles. These institutional arrangements are perceived to support more coordinated victim assistance, legal processes, and access to psychological and social services. Nevertheless, several challenges remain evident, including limited human resources, administrative constraints, and difficulties in obtaining accurate information from traumatized victims. Since the findings primarily reflect institutional perspectives, they do not comprehensively represent survivor experiences or the perspectives of non-governmental organizations, healthcare providers, and other external actors. This study concludes that strengthening institutional capacity, improving coordination mechanisms, and expanding survivor-centered support services remain essential for enhancing the sustainability of collaborative governance in rape case handling.